The relationship between organizational commitment and job performance among employees at Institut Pendidikan Guru Kampus Tun Abdul Razak, Kota Samarahan, Kuching, Sarawak/ Karmelisa Esmade - Esmade, Karmelisa (2018)
The purpose of this paper is to examine the relationship between organizational commitment and job performance among public sector employee working in IPGKTAR, Kota Samarahan, Sarawak. The personal opinions of the employees were analysed through the distribution of 118 sets of questionnaire. The research design used for this study was correlational research design. As for sampling technique, non-probability sampling was used to identify the respondents. The respondents involved were supporting staff, secretaries, clerks, receptionist and academic staff that work in IPGKTAR, Kota Samarahan. It is hypothesized that organizational communication has positive influence on job performance. Affective commitment, continuance commitment and normative commitment plays a mediating role between organizational commitment and job performance. Results were analysed to be correlations, it was found that organizational commitment shows significant positive relation with job performance. Among the three independent variable in organizational commitment, the study found continuance commitment has moderate relationship with job performance compared to normative and affective commitment which both variable shows strong relationship with job performance. This paper also presents limitation and direction for future research.